2022
DOI: 10.1038/s42003-022-03524-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of exceptional lifespan increase of Drosophila melanogaster with different genotypes after combinations of pro-longevity interventions

Abstract: Aging is one of the global challenges of our time. The search for new anti-aging interventions is also an issue of great actuality. We report on the success of Drosophila melanogaster lifespan extension under the combined influence of dietary restriction, co-administration of berberine, fucoxanthin, and rapamycin, photodeprivation, and low-temperature conditions up to 185 days in w1118 strain and up to 213 days in long-lived E(z)/w mutants. The trade-off was found between longevity and locomotion. The transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 108 publications
3
5
2
Order By: Relevance
“…Our results unambiguously reinforce that DR can reliably increase lifespan in flies at standard lab conditions across different temperatures. As such our work fits with earlier work that used a combination of life-extending treatments, including temperature and DR, and found them to be largely additive (Kim et al, 2020; Shaposhnikov et al, 2022). Our findings and this prior literature contradict those of a recent study (Zajitschek et al, 2023) and counter their argument that DR constitutes a lab artefact.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results unambiguously reinforce that DR can reliably increase lifespan in flies at standard lab conditions across different temperatures. As such our work fits with earlier work that used a combination of life-extending treatments, including temperature and DR, and found them to be largely additive (Kim et al, 2020; Shaposhnikov et al, 2022). Our findings and this prior literature contradict those of a recent study (Zajitschek et al, 2023) and counter their argument that DR constitutes a lab artefact.…”
Section: Discussionsupporting
confidence: 88%
“…That a clear positive control, namely DR extending lifespan consistently, is missing further limits what we can interpret from this prior study. Our work here, supported by prior published work by others (Kim et al, 2020;Shaposhnikov et al, 2022), does not support the interpretation that DR is a lab artefact and that DR would therefore not extend lifespan in the wild (Zajitschek et al, 2023). Even though conditions, environmental or genetic, that modulate the DR response are a valuable tool forward to understanding the DR response and ageing more generally (Simons & Dobson, 2023), it deters progress if such contrary findings are overinterpreted, especially when they are interpreted to have a broader ecological, evolutionary and physiological relevance.…”
Section: Discussionsupporting
confidence: 88%
“…In this regard, Shaposhnikov et al . recently demonstrated a synergistic effect by targeting multiple aging hallmarks simultaneously, producing a significant increase in Drosophila melanogaster lifespan compared to single interventions (Shaposhnikov et al ., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this line, attempts to induce multiparameter amelioration are now emerging as a strategy for rejuvenation even outside the field of cellular reprogramming. In this regard, Shaposhnikov et al recently demonstrated a synergistic effect by targeting multiple aging hallmarks simultaneously, producing a significant increase in Drosophila melanogaster lifespan compared to single interventions (Shaposhnikov et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Drosophila overwinters in nature in the adult stage in vegetable warehouses, etc., wherever the temperature reaches 16 °C. At this temperature, the duration of lifespan of adult flies is significantly lengthened [ 13 ].…”
Section: Advantages Of Drosophila As a Highly Info...mentioning
confidence: 99%